The kangaroo-mother method: mothers´ living experience in the rooming-in - Rejane Marie Barbosa Davim; Bertha Cruz Enders; Janmilli da Costa Dantas; Richardson Augusto Rosendo da Silva; Edualeide Jeane Pereira Bulhões da Nóbrega (Rev Rene)
This is a qualitative and descriptive study which aims to describe the experience of mothers who face the Kangaroo-Mother Method (KMM) in rooming-in and identify the family relationship in this process, using as a data-collection technique the focus group with recorded interviews, in two groups of kangaroo-mothers puerperas in a rooming-in of a public maternity in Natal / RN, within a week period. It was used from the thematic scrip entitled “Experience of mothers facing the KMM in rooming-in and the family engagement in this process”. Three thematic points came out of our study: Helping child in slow development; step by step; promoting contact with the baby that should still be in the womb and expecting every day for the baby’s growing and adjustment. Despite the institutional problems we face in keeping it nowadays it is still considered an effi cient method. These diffi culties can be minimized by current perinatal policies that aim the prevention of damage to premature baby’s health, offering peacefulness for the neonatal healthcare team as well as to the whole family.